2018
DOI: 10.21037/tau.2018.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lymph node metastases in penile cancer

Abstract: Penile cancer (PC) is a relatively rare malignancy in the United States (US) but a greater concern in developing nations. Lymph node imaging remains critical to the staging and treatment of this disease as metastases develop in a predictable, anatomic fashion. Early surgical intervention remains a mainstay in treatment and imaging often aids in decision making. This review highlights the indications for imaging in both low-stage and advanced disease. Furthermore, we discuss the benefits and limitations of curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…These agents are taken up by penile lymphatics and phagocytosed by resident macrophages; these macrophages are less prevalent in metastatic nodes. In a limited study with seven men (stage T1b-T2), this detection method showed sensitivity of 100%, specificity of 97%, positive predictive value of 81.2%, and negative predictive value of 100% (15,16). This provides promise as PET/CT is only 57% accurate in predicting ILNM in patients with normal groin exams compared to 96% in patients with palpable nodes (17).…”
Section: Clinical/pathological Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These agents are taken up by penile lymphatics and phagocytosed by resident macrophages; these macrophages are less prevalent in metastatic nodes. In a limited study with seven men (stage T1b-T2), this detection method showed sensitivity of 100%, specificity of 97%, positive predictive value of 81.2%, and negative predictive value of 100% (15,16). This provides promise as PET/CT is only 57% accurate in predicting ILNM in patients with normal groin exams compared to 96% in patients with palpable nodes (17).…”
Section: Clinical/pathological Factorsmentioning
confidence: 99%
“…In patients who are low-risk for ILNM, an 8mm cut-off in the CT short axis provides the most accurate detection, with a sensitivity of 87% and a specificity of 81%. For patients with high risk for ILNM, size is less accurate, and the most accurate (88%) criteria for nodal involvement is an irregular nodal border with a specificity of 95% (15). Moving away from size criteria for the evaluation of ILNM in the presence of known primary SCC of the penis is crucial, as this has the tendency to miss occult metastases in normal-sized nodes and to label reactive nodes as malignant.…”
Section: Clinical/pathological Factorsmentioning
confidence: 99%
“…These particles travel via penile lymphatics and undergo preferential phagocytosis by resident macrophages. Metastatic nodes often lack macrophages and accumulate less contrast, resulting in a brighter T2Ã-weighted signal [17]. A study of seven men with pT1b-pT2 pSCC found a sensitivity of 100%, specificity of 97%, a positive predictive value of 81.2% and a negative predictive value of 100% [18].…”
Section: Imagingmentioning
confidence: 99%
“…First, the cancer spreads to the sentinel lymph nodes, usually in the superficial lymph nodes near the central and superior aspects of the saphenofemoral junction, then progresses to the inferior and deep inguinal nodes, and finally to the pelvic nodes. 6 Presence of inguinal lymph node metastasis (LNM) is one of the most significant prognostic factors for patients with penile cancer. 7 The 5-year survival percentage of penile cancer patients decreases according to the regional LNMs as follows: from 90% to 100% in no involvement of lymph nodes (pN0) to 80% in unilateral lymph nodes (pN1), 40% in multiple unilateral or bilateral inguinal lymph nodes (pN2), and only 11% in patients with already involved fixed inguinal or pelvic lymph nodes (pN3).…”
Section: Introductionmentioning
confidence: 99%